2006
DOI: 10.1590/s0004-27302006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Modelos experimentais de resistência à insulina e obesidade: lições aprendidas

Abstract: For better understanding the role of each element involved in the physiopathology of obesity and insulin resistance, researchers can use experimental models, which may in controlled manner evaluate the participation of each element on the obesity and insulin resistance and provide information for better understanding the physiopathology and treatment of obesity and insulin resistance. Experimental obesity and insulin resistance can be due to a deficient response to leptin, secondary to hypoleptinemia and/or mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
11
0
7
Order By: Relevance
“…[16][17][18][19][20][21] According to the results obtained in the second stage of the study, there was no statistically significant difference between the groups regarding weight gain, which is similar to the findings obtained in a study by Fernandes et al, 22 where no significant difference was found in the weight gain of animals in the groups given a diet supplemented with 1% of conjugated linoleic acid (CLA) compared to the groups that were not given the referred supplement. This finding is also corroborated by the study by Bhattachaya et al, 23 where BALB/C mice fed with a high-fat diet supplemented with 0.4% of CLA showed no change in body weight.…”
Section: -Body Weight Gain (A) Weight Of Total Adipose Tissue (B) Esupporting
confidence: 88%
See 1 more Smart Citation
“…[16][17][18][19][20][21] According to the results obtained in the second stage of the study, there was no statistically significant difference between the groups regarding weight gain, which is similar to the findings obtained in a study by Fernandes et al, 22 where no significant difference was found in the weight gain of animals in the groups given a diet supplemented with 1% of conjugated linoleic acid (CLA) compared to the groups that were not given the referred supplement. This finding is also corroborated by the study by Bhattachaya et al, 23 where BALB/C mice fed with a high-fat diet supplemented with 0.4% of CLA showed no change in body weight.…”
Section: -Body Weight Gain (A) Weight Of Total Adipose Tissue (B) Esupporting
confidence: 88%
“…14,15 However, the animal model that most resembles the etiology of human obesity is the one involving high intake of dietary fat. 16 However, the extrapolation of many of these animal models to human obesity …”
Section: Discussionmentioning
confidence: 99%
“…Os períodos de administração da dieta descritos na literatura variaram de duas a 13 semanas (7,(11)(12)(13)(14)(15)(16)28,30,31,33) ; muitos desses estudos utilizaram ratos da linhagem Sprague-Dawley (2,7,10,12,13,28,30,31) ou cepa SHR -ratos espontaneamente hipertensos (37) . A resposta do lactato sanguíneo durante o teste de esforço permitiu determinar a MFEL em ambos os grupos.…”
Section: Discussionunclassified
“…The monosodium glutamate is a substance commonly used in the food industry to enhance the food flavor. However, this substance is neurotoxic and the excess of monosodium glutamate in the brain allows high affluence of calcium inside the neuronal cell, providing the formation of free radicals (FR) with cell death (Natali, 2001;Cesaretti, 2006). The oxidative stress damage is minimized by the antioxidant defense system and can be classified as natural or synthetic (Jones, 2008;Halliwel, 2007).…”
Section: Introductionmentioning
confidence: 99%